Chemogenomics identifies acetyl-coenzyme A synthetase as a target for malaria treatment and prevention. Issue 2 (17th February 2022) - Summers, Robert L.; Pasaje, Charisse Flerida A.; Pisco, Joao P.; Striepen, Josefine; Luth, Madeline R.; Kumpornsin, Krittikorn; Carpenter, Emma F.; Munro, Justin T.; Lin, De; Plater, Andrew; Punekar, Avinash S.; Shepherd, Andrew M.; et al.
Summary: We identify the Plasmodium falciparum acetyl-coenzyme A synthetase ( Pf AcAS) as a druggable target, using genetic and chemical validation. In vitro evolution of resistance with two antiplasmodial drug-like compounds (MMV019721 and MMV084978) selects for mutations in Pf AcAS. Metabolic profiling of compound-treated parasites reveals changes in acetyl-CoA levels for both compounds. Genome editing confirms that mutations in Pf AcAS are sufficient to confer resistance. Knockdown studies demonstrate that Pf AcAS is essential for asexual growth, and partial knockdown induces hypersensitivity to both compounds. In vitro biochemical assays using recombinantly expressed Pf AcAS validates that MMV019721 and MMV084978 directly inhibit the enzyme by preventing CoA and acetate binding, respectively. Immunolocalization studies reveal that Pf AcAS is primarily localized to the nucleus. Functional studies demonstrate inhibition of histone acetylation in compound-treated wild-type, but not in resistant parasites. Our findings identify and validate Pf AcAS as an essential, druggable target involved in the epigenetic regulation of gene expression. Graphical abstract: Highlights: Mutations in Pf AcAS confer resistance to antiplasmodials MMV019721 and MMV084978 MMV019721 and MMV084978 specifically inhibit Pf AcAS by competing with substrates cKD and IFA show Pf AcAS is an essential nuclear enzyme in blood-stage parasites Pf AcAS inhibitors deplete parasite acetyl-CoA and result in histone hypoacetylation Abstract : Using chemogenomics, Summers et al. identify PfAcAS as the target of two antimalarial compounds, MMV019721 and MMV084978. Pf AcAS is an essential, nuclear-localized enzyme responsible for acetyl-CoA biosynthesis in blood-stage parasites. Both compounds inhibit Pf AcAS competitively and act by depleting acetyl-CoA and disrupting histone acetylation in the parasite.